Trademark Registration As A Legal Protection Effort For MSME Products - Asep Hakim Zakiran; Mentari Jastisia; Belardo Prasetya Mega Jaya (Fakultas Hukum, Universitas Islam Bandung, 2022)
MSMEs in Indonesia have enormous potential to support economic growth. It is because the number of MSMEs in Indonesia reaches 99.9% of all businesses operating in Indonesia. However, the high number of MSMEs in Indonesia has not been followed by the level of awareness of MSME actors to register their business brands. The purpose of this study is to determine the legal protection that MSMEs can obtain for their trademark registration. The method used in this research is normative juridical. The results of this study indicate that there are various benefits of registration, both preventive and repressive legal protection.